Thin films of Cu, In and Sb chalcogenides as photovoltaic absorbers - Ornelas Acosta, Raúl Ernesto (2015)
Many different photovoltaic technologies are being developed for large-scale solar energy conversion such as crystalline silicon solar cells, thin film solar cells based on a-Si:H, CIGS and CdTe. As the demand for photovoltaics rapidly increases, there is a pressing need for the identification of new visible light absorbing materials for thin-film solar cells. Nowadays there are a wide range of earth-abundant absorber materials that have been studied around the world by different research groups. The current thin film photovoltaic market is dominated by technologies based on the use of CdTe and CIGS, these solar cells have been made with laboratory efficiencies up to 19.6% and 20.8% respectively. However, the scarcity and high cost of In, Ga and Te can limit in the long-term the production in large scale of photovoltaic devices. On the other hand, quaternary CZTSSe which contain abundant and inexpensive elements like Cu, Zn, Sn, S and Se has been a potential candidate for PV technology having solar cell efficiency up to 12.6%, however, there are still some challenges that must be accomplished for this material. Therefore, it is evident the need to find the alternative inexpensive and earth abundant materials for thin film solar cells. One of these alternatives is copper antimony sulfide(CuSbS2) which contains abundant and non-toxic elements which has a direct optical band gap of 1.5 eV, the optimum value for an absorber material in solar cells, suggesting this material as one among the new photovoltaic materials. This thesis work focuses on the preparation and characterization of In6Se7, CuSbS2 and CuSb(S1-xSex)2 thin films for their application as absorber material in photovoltaic structures using two stage process by the combination of chemical bath deposition and thermal evaporation.